Application Of Geographically Weighted Panel Regression Based On Seasonal Pattern In Data For The Development Of Dengue Hemorrhagic Fever (DHF) In North Sumatra Province - Putri, Dinda Kusuma; Rakhmawati, Fibri (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus which is transmitted to humans through the bites of Aedes aegypti and Aedes albopictus mosquitoes which were previously infected with the dengue virus from other dengue fever sufferers. This research aims to apply the Geographically Weighted Panel Regression (GWPR) method. in identifying what factors influence the development of Dengue Hemorrhagic Fever in 33 districts in North Sumatra Province starting from September 2022-August 2023 with a rainy and dry season pattern. The results of this research show that the appropriate GWPR model is the fixed effect model with the pepmbobot kerne bisquare function. Based on this model, the districts/cities of North Sumatra are divided into ten groups based on variables with a high significant influence on the percentage of development of Dengue Hemorrhagic Fever. The factors that influence this percentage are gender, namely male and female, then Age, namely ≤ 14 Years and Age ≥ 14 Years.